A Legal Perspective on Inheritance of Joint Property: A Comparative Analysis of Various Legal Systems - Rosalina Limbong (Legal Frontier, 2025)
Joint property inheritance is a complex issue in various legal systems around the world, reflecting the different principles and approaches between Civil Law, Common Law, Islamic law, customary law, and hybrid legal systems. This research aims to comparatively analyze the legal perspectives on inheritance of joint property in various legal systems, highlighting the main principles, application in various countries, and regulatory challenges that arise. The method used is a systematic literature review, by analyzing legal documents, court decisions, and relevant academic studies. The results show that in Civil Law, the distribution of inheritance generally follows written legal rules that strictly regulate the rights of heirs, while in Common Law, testamenter freedom is dominant, although it can be corrected by the court. In Islamic law, the faraid system regulates the distribution of inheritance based on religious decree principles, while in customary law, cultural norms and community values often influence inheritance patterns. In countries with pluralistic legal systems, such as Indonesia, Malaysia and Nigeria, regulatory disharmony can lead to inheritance disputes, especially in terms of gender imbalance and jurisdictional conflicts between national, customary and religious laws. This research confirms the importance of regulatory harmonization to create a more inclusive and equitable inheritance law system. Legal reforms that accommodate gender equality, legal certainty and administrative efficiency are strategic steps in facing the challenges of inheriting joint property in the modern era. With a deeper understanding of these different legal systems, it is hoped that legal policies can be developed to reduce inheritance disputes and improve the protection of the rights of all parties involved.